(untitled) (Global Journal of Medical Research, 2019)
Uveitis is a common ocular disease characterized by inflammation of iris, choroid, and ciliary body. HLA-B27 is the strongest known genetic risk factor for acute anterior uveitis. The prevalence of HLA B27 and associated diseases varies widely across different racial groups and have massive clinical implications. DNA typing was done using amplification of genomic DNA by the polymerase chain reaction (PCR) and hybridization with sequence-specific oligonucleotide probes (SSOP). This study was undertaken due to paucity of recent reports on Asian Indian population with uveitis as a predominant clinical feature.